Systematics and Plastome Evolution in Schizaeaceae - Ke, Bing-Feng; Wang, Goang-Jiun; Labiak, Paulo H.; Rouhan, Germinal; Chen, Cheng-Wei; Shepherd, Lara D.; Ohlsen, Daniel J.; Renner, Matthew A. M.; Karol, Kenneth G.; Li, Fay-Wei; Kuo, Li-Yaung (Frontiers in Plant Science, 2022)
While the family Schizaeaceae (Schizaeales) represents only about 0.4% of the extant fern species diversity, it differs from other ferns greatly in gross morphologies, niche preferences, and life histories. One of most notable features in this family is its mycoheterotrophic life style in the gametophytic stage, which appears to be associated with extensive losses of plastid genes. However, the limited number of sequenced plastomes, and the lack of a well-resolved phylogenetic framework of Schizaeaceae, make it difficult to gain any further insight. Here, with a comprehensive sampling of ~77% of the species diversity of this family, we first inferred a plastid phylogeny of Schizaeaceae using three DNA regions. To resolve the deep relationships within this family, we then reconstructed a plastome-based phylogeny focusing on a selection of representatives that covered all the major clades. From this phylogenomic backbone, we traced the evolutionary histories of plastid genes, and examined whether gene losses were associated with the evolution of gametophytic mycoheterotrophy. Our results reveal that extant Schizaeaceae is comprised of four distinct clades－Microschizaea, Actinostachys, Schizaea, and S. pusilla. The loss of all plastid NADH-like dehydrogenase (ndh) genes was confirmed to have occurred in the ancestor of extant Schizaeaceae, which coincides with the evolution of mycoheterotrophy in this family. For chlorophyll biosynthesis genes (chl), the losses are interpreted as convergent in Schizaeaceae, and found not only in Actinostachys, a clade producing achlorophyllous gametophytes, but also in S. pusilla with chlorophyllous gametophytes. In addition, we discovered a previously undescribed but phylogenetically distinct species hidden in the Schizaea dichotoma complex, and provided a taxonomic treatment and morphological diagnostics for this new species－Schizaea medusa. Finally, our phylogenetic results suggest that the current PPG I circumscription of Schizaea is non-monophyletic, and we therefore proposed a three-genus classification moving a subset of Schizaea species sensu PPG I to a third genus－Microschizaea.